Vaccination of village chickens in The Gambia against Newcastle disease using the heat‐resistant, food‐pelleted V4 vaccine - Jagne, Jarra; Aini, I.; Schat, K. A.; Fennell, A.; Touray, O. (1991)
The Australian non-pathogenic, heat-resistant V4strain of Newcastle disease virus (NDV) in food-pellet form was used on a single occasion to vaccinate village poultry in The Gambia. The response of the chickens to the vaccine virus was monitored with the haemagglutination inhibition (HI) test. Pre-vaccination HI tests showed that the majority of chickens tested did not have antibodies to NDV. At 4 and 12 weeks post-vaccination, vaccinated chickens showed 30 and 48% seroconversion, respectively. The HI titres were indicative of protection, but challenge experiments were not undertaken. Only a low percentage of the control groups were antibody positive at these times. © 1991, Taylor & Francis Group, LLC. All rights reserved.